A new species of Eurypeza Lacroix, 2006 (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) from Kenya - Sehnal, Richard (Zootaxa, 2017)
The Afrotropical genus Eurypeza Lacroix, 2006 (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) was established for one species, Eurypeza evansi Lacroix, 2006, from Somalia. The genus belongs to the first group of Afrotropical Tanyproctini sensu Lacroix (2007), and is characterized by protarsomeres 1–4 and mesotarsomeres 1–4 broadened and ventrally macrosetaceous, protarsomere 5 and mesotarsomere 5 simple, and labrum transverse and shallowly bilobed. The genus Eurypeza differs from other genera of Lacroix’s (2007) first group by club with five antennomeres, antennomere 3 and 4 of equal length, labial palpi with three palpomeres, clypeus broadly rounded, protibia bidentate with proximal tooth well developed, and metatibial carina incomplete (for details, see also Lacroix 2006, 2007).